Reduced contribution of endothelin to the regulation of systemic and pulmonary vascular tone in severe familial hypercholesterolaemia. (13th February 2014) - Bender, Shawn B.; de Beer, Vincent J.; Tharp, Darla L.; van Deel, Elza D.; Bowles, Douglas K.; Duncker, Dirk J.; Laughlin, M. Harold; Merkus, Daphne
Abstract : Key points: Familial hypercholesterolaemia (FH) causes vascular dysfunction involving reduced nitric oxide (NO) bioavailability and limits exercise‐induced vasodilatation in the systemic, but not pulmonary, vasculature. The mechanism(s) underlying blunted exercise‐induced systemic vasodilatation in FH are unclear but may involve enhanced endothelin‐1 (ET‐1)‐mediated vasoconstriction resulting from lessened NO‐dependent inhibition. In a chronically instrumented swine model of FH, ET‐1 receptor inhibition in vivo did not restore systemic exercise‐induced vasodilatation but rather revealed a reduced role for ET‐1 in regulating systemic and pulmonary vascular tone at rest and during exercise associated with reduced circulating ET‐1 in FH swine. In contrast, isolated skeletal muscle arterioles from FH swine exhibited enhanced ET‐1 sensitivity due to reduced NO with no change in smooth muscle ET receptor expression. These results increase understanding of FH‐associated vascular dysfunction by revealing a novel reduction in ET production and resultant attenuation of ET‐dependent vascular tone in vivo in FH. Abstract: Vascular dysfunction has been associated with familial hypercholesterolaemia (FH), a severe form of hyperlipidaemia. We recently demonstrated that swine with FH exhibit reduced exercise‐induced systemic, but not pulmonary, vasodilatation involving reduced nitric oxide (NO) bioavailability. Since NO normally limits endothelin (ET) action, we examined the hypothesis that reduced systemic vasodilatation during exercise in FH swine results from increased ET‐mediated vasoconstriction. Systemic and pulmonary vascular responses to exercise were examined in chronically instrumented normal and FH swine in the absence and presence of the ETA/B receptor antagonist tezosentan. Intrinsic reactivity to ET was further assessed in skeletal muscle arterioles. FH swine exhibited ∼9‐fold elevation in total plasma cholesterol versus normal swine. Similar to our recent findings, systemic, not pulmonary, vasodilatation during exercise was reduced in FH swine. Blockade of ET receptors caused marked systemic vasodilatation at rest and during exercise in normal swine that was significantly reduced in FH swine. The reduced role of ET in FH swine in vivo was not the result of decreased arteriolar ET responsiveness, as responsiveness was increased in isolated arterioles. Smooth muscle ET receptor protein content was unaltered by FH. However, circulating plasma ET levels were reduced in FH swine. ET receptor antagonism caused pulmonary vasodilatation at rest and during exercise in normal, but not FH, swine. Therefore, contrary to our hypothesis, FH swine exhibit a generalised reduction in the role of ET in regulating vascular tone in vivo probably resulting from reduced ET production. This may represent a unique vascular consequence of severe familial hypercholesterolaemia.